Reversing Negative Trends in Spare Parts Control - Fernando W.A.M.A.R; Jinadasa U.G.O.C; Amarasinghe B.P.A; Mandalawatta M.T; D.I de Silva; Dulanji Cooray (International Journal of Engineering and Management Research, 2022)
The consumer SPARE BROTHERS’ a Colombo, Sri Lanka company, commissioned the implementation of the online e-commerce management system. The users currently manage its employees’ significant amounts of data manually using a manual approach. The suggested solution enables consumers to store and manage data in own database, greatly improving the efficiency of their data handling methods. The suggest system is designed to handle all the steps involved in managing a spare parts business, including consumer, store, cart, payment, delivery, order, and rider management. Firstly, if a user is already a consumer, user can connect to the system with users’ credentials and be redirected to user’s responsible side. If not, user can sign up for the system. Here, it includes with this system set up as a distinct site for the user and the administrator. The system’s spare parts can be added by the admin, and those parts will then appear on the user side. Hence that consumer can purchase products based on user’s interests. Users can manage cart items here, and if user’s wish to proceed to check out, users can enter own payment and delivery details. After the order is complete, the administrator can designate a rider to transport those things to the appropriate location. Lastly, the admin can edit, delete, and generate certain essential reports to manage all the user, product, order, delivery, and rider details. Consequently, the administrator can add notifications, search relevant categories, and allow users to add wish lists. The solution decreases data manipulation errors in the present process, leading to a significant improvement in the utilization of human resources. It enhances consumers’ interactions with their customers, increasing revenue for the company. The process is simple to use, dependable, and effective, and its statistics meet the needs of consumers.